The Influence of Arm Muscle Strength, Hand Eye Coordination and Concentration on the Free Trow Ability of Binuang Sakti Basketball Athletes in Sijunjung Regency - Fitrya Mustika Andriani; Willadi Rasyid; Hendri Neldi; Muhammad Sazeli Refki (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The aim of this study was to analyze the effect of arm muscle strength, eye-hand coordination and concentration on the free throw ability of the Binuang Sakti basketball athletes in Sijunjung district. This research is a type of path analysis research. This research was carried out in the Sibinuang Sakti Basketball Court, Sijunjung Regency. The population comes from all basketball athletes in Sijunjung Regency totaling 41 people. The samples came from basketball athletes, totaling 26 people. The sampling technique in this research is purposive sampling. The data analysis technique was descriptive statistical analysis using SPSS version 16. The results showed that there was a significant effect of arm muscle strength, eye-hand coordination and concentration on the free throw ability of basketball athletes in Binuang Sakti, Sijunjung district.